Transition risks and opportunities in residential mortgages - Franziska Schütze (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
A range of studies has analysed how climate-related risks can impact financial markets, focusing on equity and corporate bond holdings. This article takes a closer look at transition risks and opportunities in residential mortgages. Mortgage loans are important from a financial perspective due to their large share in banks' assets and their long credit lifetime, and from a climate perspective due to their large share in fossil fuel consumption. The analysis combines data on the energy-performance of buildings with financial data on mortgages for Germany and identifies two risk drivers - a carbon price and a performance standard. The scenario analysis shows that expected credit loss can be substantially higher for a "brown" portfolio compared to a "green" portfolio. Taking climate policy into account in risk management and strategy can reduce the transition risk and open up new lending opportunities. Financial regulation can promote such behaviour.
Keywords: G21; Q48; Q56; Q58; R38; 330; Mortgages; Residential Buildings; Carbon Risks; Transition Risks; Valuation; Climate Policy Scenarios; Policy and Regulation